Arabidopsis Elongator subunit 2 positively contributes to resistance to the necrotrophic fungal pathogens Botrytis cinerea and Alternaria brassicicola. (17th August 2015) - Wang, Chenggang; Ding, Yezhang; Yao, Jin; Zhang, Yanping; Sun, Yijun; Colee, James; Mou, Zhonglin
Summary The evolutionarily conserved Elongator complex functions in diverse biological processes including salicylic acid‐mediated immune response. However, how Elongator functions in jasmonic acid (JA)/ethylene (ET)‐mediated defense is unknown. Here, we show that Elongator is required for full induction of the JA/ET defense pathway marker gene PLANT DEFENSIN1.2 (PDF1.2) and for resistance to the necrotrophic fungal pathogens Botrytis cinerea and Alternaria brassicicola. A loss‐of‐function mutation in the Arabidopsis Elongator subunit 2 (ELP2) alters B. cinerea‐induced transcriptome reprogramming. Interestingly, in elp2, expression of WRKY33, OCTADECANOID‐RESPONSIVE ARABIDOPSIS AP2/ERF59 (ORA59), and PDF1.2 is inhibited, whereas transcription of MYC2 and its target genes is enhanced. However, overexpression of WRKY33 or ORA59 and mutation of MYC2 fail to restore PDF1.2 expression and B. cinerea resistance in elp2, suggesting that ELP2 is required for induction of not only WRKY33 and ORA59 but also PDF1.2. Moreover, elp2 is as susceptible as coronatine‐insensitive1 (coi1) and ethylene‐insensitive2 (ein2) to B. cinerea, indicating that ELP2 is an important player in B. cinerea resistance. Further analysis of the lesion sizes on the double mutants elp2 coi1 and elp2 ein2 and the corresponding single mutants revealed that the function of ELP2 overlaps with COI1 and is additive to EIN2 for B. cinerea resistance. Finally, basal histone acetylation levels in the coding regions of WRKY33, ORA59, and PDF1.2 are reduced in elp2 and a functional ELP2‐GFP fusion protein binds to the chromatin of these genes, suggesting that constitutive ELP2‐mediated histone acetylation may be required for full activation of the WRKY33/ORA59/PDF1.2 transcriptional cascade.